Education and Literature: contributions of the literary work O Uraguai in brazilian education - Santiago, Amanda da Conceição; Dias, Dilma Costa Nogueira; Rocha Filho, Ulysses (The ESPecialist, 2024)
In cultural studies applied to literature, we identify the context of the time of narrative discourse, mythology resignified, as well as historical, social and cultural debates about the fictional process. In this literary thought, we list literature for discussion and understanding of the reality presented, in the sense of dialogue with critical, romantic and/or realistic debates. In view of this, I presented, in light of the importance of literature and the interpretative bias, developing pressing aspects of the book O Uraguai: an epic poem that brings with it the history of a period of war, revealing to us ideological traits of the author who, despite being Jesuit, exalts, in his work, the Portuguese Marquês de Pombal who is in the fight against indigenous people and Jesuits. The territorial dispute and colonialism represented in the work are still present today, leading us to the conclusion that discussions on these subjects need to be expanded so that we reach the school environment, since the chronologies pointed out in the aforementioned poem are current, even though the history of the indigenous people Caçambo and Lindoya in opposition to the Jesuit Balda are adapted to the Brazilian reality of the 18th century.